Leveraging islamic banking and finance for small business: Exploring the conceptual and practical dimensions - Mohd Thas Thaker, M. A.; Mohd Thas Thaker, Hassanudin *; Anwar, A. P.; Amin, M.; Ahmad, K. (Asian Development Bank Institute, 2020)
Small businesses are considered one of the sources of innovation, productivity and dynamism in many countries. Thus, to translate innovative ideas into sustainable businesses, access to capital becomes a part and parcel of their business lifecycle. Despite their potential importance for economic development, small businesses are facing difficulties in attracting external finance at the early and middle stages of the entrepreneurial lifecycle in many countries, including developed and developing countries. As a response, the Addis Ababa Action Agenda on Financing for Development (2015) recognized the role of additional financing, in particular using innovative mechanisms, instruments and modalities. It encourages mechanisms based on models combining public and private resources (blended finance) and joint ventures that bring significant impact investing. In line with this, Islamic banking and finance is a broad framework that has great potential for supporting development finance particularly related to small business, given their fundamental criteria emphasizing generating positive societal impact. The main objectives covered by this paper are: (i) to perform a landscape analysis of financing small business for selected Asian countries, particularly Malaysia and Indonesia; (ii) to identify and unpack innovative financing opportunities within Islamic banking and finance instruments such as Mudharabah (profit-sharing), Musharakah (profit-loss sharing), Murabahah (sale with cost plus profit margin, Ijarah [Islamic leasing]), and Salam (forward sale) as potential solutions for addressing small businesses’ funding gaps; and (iii) to initiate the development of systematic principles for the utilization of Islamic banking and finance instruments in financing small businesses.